Natural geochemical markers reveal environmental history and population connectivity of common cuttlefish in the Atlantic Ocean and Mediterranean Sea - Rooker, Jay R. (2020)
Natural markers (delta C-13 and delta O-18 stable isotopes) in the cuttlebones of the European common cuttlefish (Sepia officinalis) were determined for individuals collected across a substantial portion of their range in the Northeast Atlantic Ocean (NEAO) and Mediterranean Sea. Cuttlebone delta C-13 and delta O-18 were quantified for core and edge material to characterize geochemical signatures associated with early (juvenile) and recent (sub-adult/adult) life-history periods, respectively. Regional shifts in cuttlebone delta C-13 and delta O-18 values were detected across the 12 sites investigated. Individuals collected from sites in the NEAO displayed more enriched delta C-13 and delta O-18 values relative to sites in the Mediterranean Sea, with the latter also showing salient differences in both markers among western, central and eastern collection areas. Classification success based on cuttlebone delta C-13 and delta O-18 values to four geographical regions (NEAO, western, central and eastern Mediterranean Sea) was relatively high, suggesting that environmental conditions in each region were distinct and produced area-specific geochemical signatures on the cuttlebones ofS. officinalis. A modified delta C-13 and delta O-18 baseline was developed from sites proximal to the Strait of Gibraltar in both the NEAO and Mediterranean Sea to assess potential mixing through this corridor. Nearly, all (95%) of delta C-13 and delta O-18 signatures ofS. officinaliscollected in the area of the NEAO closest to the Strait of Gibraltar (Gulf of Cadiz) matched the signatures of specimens collected in the western Mediterranean, signifying potential movement and mixing of individuals through this passageway. This study extends the current application of these geochemical markers for assessing the natal origin and population connectivity of this species and potentially other taxa that inhabit this geographical area.